Pengaruh Kemampuan, Minat, Motivasi Kerja, Umpan Balik Terhadap Kinerja Karyawan Dengan Religiusitas Sebagai Variabel Moderasi - Bella Safira,; Ahmad Habibi,; Siska Yuli Anita, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Based on the results of a preliminary survey at BSI KCP Tanggamus, the information above shows that there are still many employees who are not satisfied with the feedback they receive. This early information needs to be interpreted by the division responsible for managing human resources so that employee performance can be optimal and can work optimally. This research aims to identify the influence of expertise, attention, work motivation, and feedback on the performance of Bank BSI KCP Tanggamus employees. This research uses a quantitative methodology and information collection is attempted by survey using a questionnaire. The population in this study were Bank BSI KCP Tanggamus employees. The illustration of this research was 15 people using SPSS type 20. The results of the research show that the performance of Bank BSI KCP Tanggamus employees is influenced by talent, attention, work motivation, and feedback, with aspects of religious moderation.